Exploring the complexities of sand dune transformation: the role of anthropogenic degradation and climatic conditions - Askhat, Naushabayev; Zhu, Kai; Bekzat, Rsymbetov; Tursunay, Vassilina; Nurzikhan, Seitkali; Daniyar, Dosmanbetov; Yersultan, Songulov; Kurmanbek, Zhanymhan; Issakov, Yerlan; Antal, Sándor; Ujj, Apolka; Dávid, Lóránt Dénes (Frontiers in Earth Science, 2023)
The sandy soils of the arid Southern Balkhash region have undergone anthropogenic degradation, resulting in their transformation into bare mobile sand dunes. This transformation has caused significant obstacles to the growth of the feed base of cattle breeding, particularly in areas with high concentrations of economic activity. As a consequence, the socio-economic situation of the local population has been significantly worsened. The main goal of this study was to investigate the relationship between the seasonal mobility of sand dune landforms and their hydrothermal regimes, along with the climatic conditions of the region. Our findings revealed that a fresh-sided layer of sand actively supplies the windward part of the sand dune to the leeward one during the summer months when dominant north-east, north-north-east winds blow, averaging 20.4-26.7 days per month at a speed of 3.0-3.7 m/s and breakthroughs up to 11.90-13.3 m/s, amidst very low humidity, high air temperature, and slight atmospheric precipitation. As a result, the moisture of sand in the surface root layer (0-20 cm) of the sand dune accumulation zone dropped to 0.2% in the middle and at the end of summer. These results will provide a theoretical basis for the development of effective technologies to rehabilitate the anthropogenic degradation foci of desert sandy soils that have transformed into mobile sands.